Catalyst system for preparing phthalide by oxidizing o-xylene and application of catalyst system
By combining transition metal ions and carbon nanotubes in the catalyst, using the charge transfer characteristics of carbon nanotubes and the excitation effect of transition metal ions, the problems of high cost and low selectivity of precious metal catalysts are solved, and the high selectivity of phenylene is achieved Preparation, with good industrial application prospects.
Patent Information
- Application Number
- CN202310776355.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2043-06-28
AI Technical Summary
In the prior art, noble metal catalysts have high cost, and transition metal catalysts have low conversion and selectivity in the process of oxidizing orthoxylene to phenylene, making it difficult to effectively improve the selectivity of phenylene.
Using a catalyst system including at least two transition metal ions and carbon nanotubes, the highly graphitized characteristics of carbon nanotubes and regular six-membered ring charge transfer are used to stimulate free radicals in combination with transition metal ions, inhibit excessive oxidation and improve the selection of phenylene. sex.
The selectivity of phenylene is significantly improved, with a selectivity of more than 75%, and has good industrial application prospects.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparing phthalide by oxidation, and specifically relates to a catalyst system for preparing phthalide by oxidizing o-xylene and application thereof. Background Art
[0002] Phthalide, also known as o-hydroxymethylbenzoic acid lactone, is an intermediate of fine chemicals and has a wide range of applications in medicine. It can also be used in the synthesis of dye intermediates such as 1,4-dichloroanthraquinone and 1-chloroanthraquinone. In the existing synthesis route, the raw material phthalic anhydride is the oxidation product of o-xylene. Controlling the oxidation process of o-xylene to directly obtain phthalide will be a very competitive route.
[0003] At present, the oxidation of o-xylene to phthalide mainly adopts metal catalysts such as precious metals or transition metals, but the cost of precious metal catalysts is too high, and transition metal catalysts have the problems of low o-xylene conversion rate and phthalide selectivity. For example, CN108794439A discloses a method for preparing phthalide, which uses o-xylene as a substrate and catalytically oxidizes o-xylene to phthalide under the action of transition metals and solid acid catalysts. The conversion rate of o-xylene in this method is low, only about 30%. Summary of the invention
[0004] In view of the above problems in the prior art, the present invention provides a catalyst system for preparing phthalide by oxidizing o-xylene. The catalyst system can effectively improve the selectivity of phthalide in the reaction of preparing phthalide by oxidizing o-xylene.
[0005] In a first aspect, the present invention provides a catalyst system for oxidizing o-xylene to prepare phthalide, comprising at least two transition metal ions and carbon nanotubes.
[0006] The carbon nanotubes in the catalyst system provided by the present invention have the characteristic of being highly graphitized, and the carbon atoms in the regular six-membered rings can quickly transfer charges, and can quickly excite free radicals in combination with transition metal ions to cause an immediate oxidation reaction. At the same time, the excessive oxidation catalyzed by the transition metal ions can be suppressed, so that the substrate is completely oxidized to generate diacids or CO2, thereby improving the selectivity of phthalide.
[0007] In some embodiments, the carbon nanotubes are selected from at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.
[0008] In some embodiments, the aspect ratio of the carbon nanotubes is 125-12500. In some embodiments, the aspect ratio of the carbon nanotubes is 200, 500, 750, 1000, 1250, 1500, 1750, 2000, 2250, 2500, 2750, 3000, 3250, 3500, 3750, 4000, 4250, 4500, 4750, 5000, 5250, 5500, 5750, 6000, 7250, 7500, 7750, 8000, 8500, 9000, 9500, 10000, 11000, 12000 or any value therebetween. In some embodiments, the aspect ratio of the carbon nanotubes is 2000-4000.
[0009] In some embodiments, the outer diameter of the carbon nanotube is 8nm-80nm. When the outer diameter of the carbon nanotube is too small, the charge transfer process of the carbon nanotube is short-range and effective, and it is difficult to cooperate with metal ions in a macroscopic range, thereby reducing the selectivity of phthalide. When the outer diameter of the carbon nanotube is too large, metal ions easily enter the interior of the tube, causing internal diffusion control, thereby reducing the selectivity of phthalide.
[0010] In some embodiments, the outer diameter of the carbon nanotube is 9nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, 23nm, 25nm, 27nm, 29nm, 30nm, 32nm, 34nm, 36nm, 38nm, 40nm, 43nm, 45nm, 47nm, 50nm, 53nm, 55nm, 57nm, 60nm, 63nm, 65nm, 67nm, 70nm, 73nm, 75nm, 77nm or any value therebetween. In some embodiments, in some embodiments, the outer diameter of the carbon nanotube is 10nm-30nm.
[0011] In some embodiments, the length of the carbon nanotube is 1 μm-100 μm. If the length of the carbon nanotube is too small, the charge transfer process of the carbon nanotube will be short-range effective, and it will be difficult to cooperate with metal ions in a macroscopic range, thereby reducing the selectivity of phthalide. When the length of the carbon nanotube is too large, transition metal ions are easily adsorbed on the surface of the carbon tube to form a supported catalyst, which changes the homogeneous reaction mechanism of the transition metal ions, thereby reducing the selectivity of phthalide.
[0012] In some embodiments, the length of the carbon nanotube is 5 μm, 10 μm, 15 μm, 20 μm, 23 μm, 25 μm, 27 μm, 29 μm, 30 μm, 33 μm, 35 μm, 37 μm, 39 μm, 40 μm, 43 μm, 45 μm, 47 μm, 49 μm, 50 μm, 53 μm, 55 μm, 57 μm, 59 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm or any value therebetween. In some embodiments, the length of the carbon nanotube is 20 μm-40 μm.
[0013] In some embodiments, the transition metal ions include at least two of iron ions, cobalt ions, and manganese ions. In some embodiments, the transition metal ions are selected from Fe 2+ / Fe 3+ , Fe 2+ / Co 2+ 、Co 2+ / Mn 2+ and Fe 2+ / Mn 2+ At least one of .
[0014] In some embodiments, the transition metal ion comprises a first transition metal ion and a second transition metal ion, wherein the molar ratio of the first transition metal ion to the second transition metal ion is (0.1-10): 1. In some embodiments, the molar ratio of the first transition metal ion to the second transition metal ion is 0.5:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1 or 9:1.
[0015] In some embodiments, the first transition metal ion is selected from Fe 2+ , Fe 3+ 、Co 2+ or Mn 2+ In some embodiments, the second transition metal ion is selected from Fe 2+ , Fe 3+ 、Co 2+ or Mn 2+ One of them.
[0016] In a second aspect, the present invention provides use of the catalyst system described in the first aspect in the oxidation of o-xylene to produce phthalide.
[0017] In a third aspect, the present invention provides a method for preparing phthalide by oxidizing o-xylene, which comprises reacting o-xylene with an oxidant in the presence of the catalyst system of the first aspect.
[0018] In some embodiments, the mass ratio of the carbon nanotubes to the o-xylene is (0.01-0.1): 1. When the content of the carbon nanotubes is too low, the problem of inhibiting the transition metal ion catalytic oxidation transition cannot be solved, thereby reducing the selectivity of phthalide. When the content of the carbon nanotubes is too high, the catalytic reaction is controlled by the content of free radicals excited by the carbon nanotubes, and the transition metal catalytic inhibition is too strong, which is also not conducive to improving the selectivity of phthalide.
[0019] In some embodiments, the mass ratio of the carbon nanotube to the o-xylene is 0.015:1, 0.02:1, 0.025:1, 0.03:1, 0.035:1, 0.04:1, 0.045:1, 0.05:1, 0.055:1, 0.06:1, 0.065:1, 0.07:1, 0.075:1, 0.08:1, 0.085:1, 0.09:1, 0.095:1 or any value therebetween. In some embodiments, the mass ratio of the carbon nanotube to the o-xylene is (0.02-0.07):1.
[0020] In some embodiments, the molar ratio of the transition metal ion to the o-xylene is (0.01-0.1): 1, for example, 0.02: 1, 0.03: 1, 0.04: 1, 0.05: 1, 0.06: 1, 0.07: 1, 0.08: 1 or 0.09: 1. In some embodiments, the molar ratio of the transition metal ion to the o-xylene is (0.02-0.06): 1.
[0021] In some embodiments, the method comprises the following steps:
[0022] S1: mixing o-xylene, carbon nanotubes and a solvent, and performing pretreatment to obtain a pretreated mixed solution;
[0023] S2: In the presence of an oxidant, the mixed solution of S1 is mixed with a soluble salt of a transition metal ion and then an oxidation reaction is carried out.
[0024] In some embodiments, the pretreatment in S1 is carried out under an inert atmosphere, such as a nitrogen atmosphere. In some embodiments, the temperature of the pretreatment in S1 is 100°C-150°C, such as 120°C, 130°C or 140°C. In some embodiments, the pressure of the pretreatment in S1 is 5bar-15bar, such as 7bar, 10bar or 12bar. In some embodiments, the time of the pretreatment in S1 is 10min-100min, such as 30min, 50min or 70min. Pretreatment under an inert atmosphere can keep the reaction starting temperature within a precise range, avoid the oxidation reaction of the reaction system in advance, cause an increase in by-products, and then cause a decrease in phthalide selectivity.
[0025] In some embodiments, the reaction temperature of the oxidation reaction in S2 is 100° C.-200° C. In some embodiments, the reaction temperature of the oxidation reaction is 140° C.-180° C.
[0026] In some embodiments, the pressure of the oxidation reaction in S2 is 1 bar to 20 bar. In some embodiments, the pressure of the oxidation reaction in S2 is 5 bar to 15 bar.
[0027] In some embodiments, the oxidation reaction time in S2 is 60 min-150 min, for example, 90 min or 120 min.
[0028] In some embodiments, the method further comprises: S3: filtering the oxidation reaction product to obtain a filtrate, and crystallizing and drying the filtrate to obtain the phthalide.
[0029] In some embodiments, the filtration is performed at a temperature of 100° C.-170° C., such as 120° C., 140° C. or 160° C. In some embodiments, the crystallization is performed at a temperature of 10° C.-40° C.
[0030] In some embodiments, the solvent is selected from acetic acid and / or ethyl acetate. Acetic acid and / or ethyl acetate are easy to separate and are not prone to produce impurities that affect separation during the reaction. In some embodiments, the transition metal ion soluble salt is selected from acetate of transition metal ions.
[0031] In some embodiments, the oxidant is selected from air.
[0032] In some embodiments, the method for preparing phthalide by oxidation of o-xylene of the present invention comprises the following specific steps:
[0033] S1: adding o-xylene, carbon nanotubes and solvent into a reaction device, introducing nitrogen into the reaction device and raising the temperature to 100° C.-150° C., for example, 140° C., and maintaining the pressure at 5 bar-15 bar, for example, 10 bar;
[0034] S2: Switching the gas, introducing air into the reaction device, then adding a soluble salt of transition metal ions and raising the temperature to 100°C-200°C, for example, 170°C for reaction;
[0035] S3: filtering the oxidation reaction product at a temperature of 100° C. to 170° C. to obtain a filtrate, and crystallizing and drying the filtrate to obtain the phthalide.
[0036] In some embodiments, the crystallization time is 2 h to 8 h. The filtrate is then crystallized at 10° C. to 40° C. for 2 h to 8 h.
[0037] In some embodiments, the drying temperature is 80° C.-150° C., and the drying time is 2 h-8 h.
[0038] Beneficial technical effects of the present invention:
[0039] The invention adopts at least two transition metal ions and a carbon nanotube composite catalyst, and exhibits high catalytic activity and high selectivity for the target product phthalide in the reaction of oxidizing o-xylene to prepare phthalide. The selectivity of phthalide is as high as more than 75%, and has good industrial application prospects. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not intended to constitute any limitation of the present invention. In addition, in the following description, the description of known structures and technologies is omitted to avoid unnecessary confusion of the concepts of the present disclosure. Such structures and technologies are also described in many publications.
[0041] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0042] The present invention will be described in detail below through examples.
[0043] Unless otherwise specified, all operations in the Examples and Comparative Examples were carried out at room temperature.
[0044] Example 1
[0045] 100 g of o-xylene (99.9 wt.%) and 5 g of carbon nanotubes (TNGM2, Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, specifically, the average outer diameter of the carbon nanotubes is 11 nm, the average length of the carbon nanotubes is 30 μm, and the aspect ratio is 2727) were added to 400 g of acetic acid solvent, and the temperature was gradually raised to 140°C in a stirred tank within 50 min while nitrogen was introduced to maintain the pressure in the tank at 10 bar. The gas was switched to air at 0.18 mol / min, and then 0.02 mol Mn was pumped in within 60 min. 2+ and 0.02molCo 2+ (Acetate) At the same time, the temperature was raised to 170°C and the reaction was continued for 120 minutes.
[0046] After the reaction was completed, the reaction solution was filtered at 150°C to remove the carbon nanotube solid. The filtrate was cooled and crystallized at 15°C for 4 hours, and then the crystallized solid was placed in an oven at 100°C and dried for 6 hours to obtain the phthalide product. Among them, the o-xylene conversion rate was 100.0 mol.%, and the phthalide selectivity was 92.1 mol.%, as shown in Table 1.
[0047] Example 2
[0048] 100 g of o-xylene (99.9 wt.%) and 5 g of carbon nanotubes (same as in Example 1) were added to 400 g of acetic acid solvent, and the temperature in the stirred kettle was gradually raised to 140°C within 50 min while nitrogen was introduced to maintain the pressure in the kettle at 10 bar. The gas was switched to air at 0.18 mol / min, and then 0.02 mol of Fe 2+ and 0.02 mol Fe 3+ (Acetate) At the same time, the temperature was raised to 170°C and the reaction was continued for 120 minutes.
[0049] After the reaction was completed, the reaction solution was filtered at 150° C. to remove the carbon nanotube solid. The filtrate was cooled and crystallized at 15° C. for 4 h, and then the crystallized solid was placed in an oven at 100° C. to dry for 6 h to obtain a phthalide product, wherein the o-xylene conversion rate was 100 mol.%, and the phthalide selectivity was 80.3 mol.%, for comparison purposes, see Table 1 for details.
[0050] Example 3 to Example 6
[0051] Except that the lengths of the carbon nanotubes used are 8 μm, 15 μm, 50 μm and 70 μm respectively, the rest are the same as in Example 1.
[0052] Example 7 to Example 10
[0053] Except that the outer diameters of the carbon nanotubes used are 9 nm, 30 nm, 50 nm and 70 nm respectively, the rest are the same as in Example 1.
[0054] Example 11 to Example 14
[0055] Except that the masses of the carbon nanotubes used are 1 g, 3 g, 7 g and 9 g respectively, the rest are the same as in Example 1.
[0056] Comparative Example 1
[0057] 100 g of o-xylene (99.9 wt.%) was added to 400 g of acetic acid solvent, and the temperature in the stirred kettle was gradually raised to 140°C within 50 min while nitrogen was introduced to maintain the pressure in the kettle at 10 bar. The gas was switched to air at 0.18 mol / min, and then 0.02 mol Mn was pumped in within 60 min. 2+ and 0.02 mol Co2+ (Acetate) At the same time, the temperature was raised to 170°C and the reaction was continued for 120 minutes.
[0058] After the reaction was completed, the reaction solution was filtered at 150°C to remove the carbon nanotube solid. The filtrate was cooled and crystallized at 15°C for 4 hours, and then the filtered solid was placed in an oven at 100°C for 6 hours to obtain a phthalide product. Among them, the o-xylene conversion rate was 100 mol.%, and the phthalide selectivity was 13.5 mol.%, as shown in Table 1.
[0059] Comparative Example 2
[0060] 100 g of o-xylene (99.9 wt.%) and 5 g of SiO2 were added to 400 g of acetic acid solvent, and the temperature in the stirred kettle was gradually raised to 140°C within 50 min while nitrogen was introduced to maintain the pressure in the kettle at 10 bar. The gas was switched to air at 0.18 mol / min, and then 0.02 mol of Mn was pumped in within 60 min. 2+ and 0.02 mol Co 2+ (Acetate) At the same time, the temperature was raised to 170°C and the reaction was continued for 120 minutes.
[0061] After the reaction was completed, the reaction solution was filtered at 150°C to remove the solid. The filtrate was cooled and crystallized at 15°C for 4 hours, and then the crystallized solid was placed in an oven at 100°C and dried for 6 hours to obtain the phthalide product. Among them, the o-xylene conversion rate was 30.4 mol.%, and the phthalide selectivity was 11.9 mol.%, as shown in Table 1.
[0062] Comparative Example 3 to Comparative Example 4
[0063] In addition to adding 0.04 mol Co 2+ 、0.04mol Mn 2+ Except for the above, the rest are the same as in Example 1.
[0064] Table 1
[0065]
[0066] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A catalyst system for the oxidation of o-xylene to prepare phthalide, comprising at least two transition metal ions and carbon nanotubes.
2. The catalyst system according to claim 1, characterized in that The carbon nanotubes are selected from at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes.
3. The catalyst system according to claim 1 or 2, characterized in that The aspect ratio of the carbon nanotubes is 125-12500, preferably 2000-4000.
4. The catalyst system according to any one of claims 1 to 3, characterized in that The outer diameter of the carbon nanotube is 8nm-80nm, preferably 10nm-30nm.
5. The catalyst system according to any one of claims 1 to 4, characterized in that The length of the carbon nanotubes is 1 μm-100 μm, preferably 20 μm-40 μm.
6. The catalyst system according to any one of claims 1 to 5, characterized in that The transition metal ions include at least two of iron ions, cobalt ions and manganese ions, preferably selected from Fe 2+ / Fe 3+ , Fe 2+ / Co 2+ 、Co 2+ / Mn 2+ and Fe 2+ / Mn 2+ At least one of .
7. The catalyst system according to any one of claims 1 to 6, characterized in that The transition metal ions include a first transition metal ion and a second transition metal ion, wherein the molar ratio of the first transition metal ion to the second transition metal ion is (0.1-10):
1.
8. The catalyst system according to claim 7, characterized in that The first transition metal ion is selected from Fe 2+ , Fe 3+ 、Co 2+ or Mn 2+ One of them.
9. The catalyst system according to claim 7 or 8, characterized in that The second transition metal ion is selected from Fe 2 + , Fe 3+ 、Co 2+ or Mn 2+ One of them.
10. Use of the catalyst system according to any one of claims 1 to 9 in the oxidation of o-xylene to produce phthalide.
Citation Information
Patent Citations
Preparation method of phthalide
CN108794439A
Supported nickel-based catalyst and its preparation method and use
CN103055883A
Catalyst for preparing phthalide through hydrogenation of phthalic anhydride, preparation method of catalyst, and method for preparing phthalide through hydrogenation of phthalic anhydride
CN106362747A
Carbon nanotube supported catalyst and preparation method thereof as well as application of carbon nanotube supported catalyst in low-temperature catalytic oxidation of CO
CN107570167A
Method for preparing phthalide through catalytic liquid phase selective oxidation
CN112778252A